2020
DOI: 10.38036/jgpp.11.4_36
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of Additively Manufactured NGVs Operated in a Small Industrial Gas Turbine

Abstract: The use of additive manufacturing (AM), for example Selective Laser Melting (SLM), is poised to spark a revolution in the way high-temperature components for gas turbines are designed, but a number of grave uncertainties remain. These lie mainly with the materials sciences, but some questions with regard to manufacturing and operating SLM-parts as hot gas path components and the demands on the tolerances of the cooling features associated therewith remain as well. In order to quantify the impact of these uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The heat transfer of AM pin fins increased as well, but not to such an extent that the thermal effectiveness (heat transfer per unit pressure loss) came close to that of cast ones. Other authors [116] did not see any appreciable difference in the temperature within the region with pin fins in additively manufactured and cast NGVs. This may also be attributed to the relative sparsity of the pin-fin array used.…”
Section: Internal Coolingmentioning
confidence: 82%
See 3 more Smart Citations
“…The heat transfer of AM pin fins increased as well, but not to such an extent that the thermal effectiveness (heat transfer per unit pressure loss) came close to that of cast ones. Other authors [116] did not see any appreciable difference in the temperature within the region with pin fins in additively manufactured and cast NGVs. This may also be attributed to the relative sparsity of the pin-fin array used.…”
Section: Internal Coolingmentioning
confidence: 82%
“…Nonetheless, the vanes used in Ref. [116] were manufactured from MAR M-509 because they were used in direct comparison with cast NGVs, which were also made from this material. Others have investigated IN939 [109], which showed that the material parameters of the AM parts differed dramatically from cast ones or those made of IN738.…”
Section: Materials' Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…Co-base alloys such as Mar-M 509 also possess improved sulfidation resistance [ 32 ]. While in many of the hot sections of engines, where blades have been replaced with Ni-base superalloys due to the improved creep resistance mechanisms in γ/γ′ microstructures, there remains a need for carbide- and solid solution-strengthened Co alloys for stationary components such as nozzle guide vanes [ 33 ]. These components encounter high temperature exposure for long periods and applied loads are low enough that thermomechanical fatigue and surface oxidation become a more important concern [ 34 ].…”
Section: Introductionmentioning
confidence: 99%